System Of Exercises for Developing Writing Skills in The EFL Learning (Texas Journal of Philology, Culture and History, 2024)
The article describes a structured system of exercises designed to enhance writing skills in English as a Foreign Language (EFL) learners. The proposed system integrates process-oriented writing tasks, task-based learning activities, and collaborative exercises, tailored to the specific needs of EFL students. Each exercise is aimed at developing key aspects of writing, such as grammar, vocabulary, coherence, and structure, while also promoting critical thinking and creativity. The study highlights the significance of scaffolding in writing instruction, where learners progress through stages of writing that build from basic sentence formation to more complex compositions. Also, peer feedback and digital tools are incorporated to foster interactive learning environments and promote student autonomy. This system of exercises is designed to address common challenges EFL learners face, such as limited vocabulary and syntactic errors, while providing opportunities for authentic communication. During the teaching process, results from implementation show significant improvement in students’ writing proficiency, engagement, and confidence. The author suggests that a well-organized system of exercises can be instrumental in developing effective writing skills in EFL learners, making it a valuable tool for educators